Factors Related to Quality of Life among Elderly During COVID-19 Pandemic - Fadila, Maulidiya; Argarini, Diah; Widiastuti, Susanti (Alta Dharma Publisher, 2022)
Introduction: The elderly are one of the age groups most affected by COVID-19, with the highest percentage of deaths due to COVID-19. Several studies have shown that during the COVID-19 pandemic, the elderly experienced a decrease in their physical and psychological health level, which could lead to changes in the quality of life among the elderly COVID-19 pandemic. Objective: The study aimed to identify factors related to the quality of life among the elderly at the Tresna Werdha Budi Mulia 3 Nursing Home during the COVID-19 pandemic. Method: This study used a cross-sectional approach. The population is elderly without mental disorders living in the Tresna Werdha Budi Mulia 3 Nursing Home. A total of 88 samples were selected using the purposive sampling technique. The instruments used are QOL-Index, WHOQOL-BREF, and DSES questionnaires. Pearson Chi-Square analysis was used to identify the relationship between variables. Result: The results showed that the five factors were physical health (p=0.000), psychological health (p=0.000), social relationships (p=0.000), environmental (p=0.000), and spirituality (p=0.000) had a significant relationship with the quality of life among the elderly. Recommendation: It is hoped that the results of this study can be used as motivation for nursing home administrators and the elderly to improve the quality of life during the COVID-19 pandemic onwards.